Konsep Kesehatan Mental Peserta Didik dalam Perspektif Psikologi Pendidikan Islam - Abdul Basir (Jurusan Tarbiyah STAI Al-Gazali Bone, 2026)
Students’ mental health is a crucial aspect of educational success, yet it often receives insufficient attention in educational practice. Academic pressure, achievement demands, and learning environment dynamics may significantly affect students’ psychological well-being. This article aims to examine the concept of students’ mental health from the perspective of Islamic educational psychology through a literature study. This research employs a qualitative descriptive approach by reviewing relevant literature, including books, scholarly journal articles, and educational policy documents. The findings indicate that educational psychology views mental health as a psychological condition that enables students to develop optimally, regulate emotions, and adapt effectively to learning environments. Meanwhile, Islamic education emphasizes the balance of physical, intellectual, and spiritual dimensions in shaping students’ personalities. The integration of educational psychology and Islamic education offers a holistic approach to fostering students’ mental health, focusing not only on academic achievement but also on emotional and spiritual well-being. This study is expected to contribute theoretically to the development of Islamic educational psychology and serve as a reference for educators in creating a humane and supportive learning environment.